A Firearms in Military Activities in the Borderland of Bohemia, Silesia and Lesser Poland in the Times of Matthias Corvinus - Strzyż, Piotr (Institute of Archaeology and Ethnology of Polish Academy of Sciences, 2017)
Matthias Corvinus, the Hungarian ruler who was also called the „Warrior King”, was carrying out very intensive policy in Central Europe. Having come to the throne of Hungary in 1458, he soon also seized Moravia, Silesia and Vienna. His wars for the throne in Prague, waged first against George of Poděbrady (1468-1471) and then against Casimir the Jagiellonian (1471-1474), led to devastating raids of Hungarian troops on, among others, Opavian Silesia and Lesser Poland. In retaliation, in the end of 1474 Jagiellonian troops invaded Silesia and for a short period of time besieged Wrocław. Furthermore, in Spring 1488 a conflict over the Duchy of Głogów broke out, which ended in a long siege of this town. An important role in the modern army of Matthias Corvinus was played by firearms. These are often mentioned by written sources from this period and numerous material traces of their use are revealed by archaeological examinations at sites which were affected by invasions.
ill. ; 29 cm
Keywords: Matthias Corvinus; Lesser Poland; Bohemian Silesia; Głogów; Muszyna; firearms